Emotions Experienced by Nurses in the Care of Terminal Heart Failure Patients - Polanowska, Marta; Krzemińska, Sylwia (Quality in Sport, 2024)
The text discusses the challenges and emotional impact of caring for patients with terminal heart failure (HF) on nurses. HF is a chronic condition leading to progressive cardiac dysfunction and hypoxia, with terminal HF marked by severe symptoms like dyspnea, edema, and fatigue. At this stage, treatment focuses on palliative care to manage symptoms and improve patient comfort, emphasizing a holistic approach that addresses physical, psychological, emotional, and spiritual needs. Nurses face significant emotional challenges, including sadness, frustration, helplessness, empathy, and compassion. These emotions can affect their psychological well-being, quality of care, and job satisfaction. The study aims to analyze these emotions and the coping strategies nurses use. Sadness and frustration stem from patient suffering and limited medical options, while empathy and compassion, though positive, can lead to emotional exhaustion and burnout.